Impact of the exploitation of medicinal plants on biodiversity conservation in Saida and El Bayadh regions, Algeria - Nasrallah, Yahia; Aouadj, Sid Ahmed; Khatir, Hadj (Biodiversity: Research and Conservation, 2020)
The aim of this study was to establish an overview of medicinal plants in the Saida and El Bayadh regions through a survey of herbalists. Our survey included more than 60 herbalists spread over the territory of two Wilayas (provinces), in an area representing more than 3% of Algerian territory. At the same time, and when conditions permitted, families were interviewedand their answers most often guided our survey. In addition, we collected information on: traditional herbalists, the most exploited species, areas of origin, periods and quantities exploited, as well as the influence of this mode of exploitationon present and future biodiversity in these regions. Analysis of the data showed that threats to the biological diversity of medicinal plants mainly included human actions and natural changes. Herbalists practise this trade mostly by inheritance and they are willing to train in the field of herbalism. The frequency of use of medicinal plants as alternative medicine is very important in the social life of populations.